Analysis of behavior and failure modes of timber beams prestressed with CFRP strips. (1st December 2022) - Halicka, Anna; Ślósarz, Szymon
Highlights: Pre-tensioned CFRP strips for timber beams strengthening change failure modes. Level of prestress influences crack pattern and "load–deflection" relationship. Difference between strip and adjoining timber strains are influenced by adhesive. With increase of load, non-linear beam behavior occurs due to timber cracking. Abstract: The article presents research on timber beams strengthened with pre-tensioned carbon fiber reinforced polymer (CFRP) strips. The prestress level was different in individual series of beams as the result of different prestressing forces introduced into the strips. The reference non-strengthened beams were also prepared. The beams were tested in four-point bending. Special attention is paid to the analysis of their failure modes and the influence of the prestress level on the crack pattern. The longitudinal strains of the strip and adjoining wood grain were also measured and their differences were analyzed. It was proved that the prestress level influences the number and length of cracks depending on the prestress level as well as the beams' stiffness and consequently their deflection. The analysis revealed that the slip between the strip and timber occurred due to the deformability of the adhesive used for strip gluing.